Pengaruh Mutu Pelayanan Terhadap Kepuasan Pasien Pendaftaran Rawat Jalan Puskesmas Sayegan - Ana dewi lukita sari (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2020)
High levels of patient satisfaction include indicators of quality health care facilities. With the high number of visits at Puskesmas Seyegan researchers want to see patient satisfaction based on the quality of service.This study aims to find out the influence of service quality with patient satisfaction in outpatient registration services at Seyegan Yogyakarta Health Center. The study was conducted at Seyegan Health Center in April-May 2020. This type of research is quantitative analytics with cross sectionaldesign. Sampling technique uses incidental sampling as many as 100 patients. Data analysis uses univariate and bivariate analysis with chi square tests. The level of patient satisfaction in The Seyegan Health Center is each majority in the category of satisfaction both on the characteristics of gender, age, education, and work. Satisfaction levels in tangible dimensions, reliability, responsiveness, assurance, and emphaty each fall into the satisfied category with an average satisfaction score of 77.45%. Calculation of the effect of service quality with patient satisfaction in outpatient registration services at Puskesmas Seyegan resulted in a p-value of 0.000. This means that ther is an influence on the quality of service with patient satisfaction in outpatient registration services at Seyegan Health Center.